2013
DOI: 10.1111/cid.12058
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Evaluate Volumetric Changes in Sinus Augmentation Procedure

Abstract: The standardization of the method allows to obtain repeatable measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…Dellavia et al [34] reported a total bone volume change of 19 % in 6 months following sinus augmentation when using a mixture of autogenous bone (30 %) and bovine bone matrix (BioOss Ò , Geistlich Pharma AG, Wolhusen, Switzerland) (70 %). Kirmeier et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dellavia et al [34] reported a total bone volume change of 19 % in 6 months following sinus augmentation when using a mixture of autogenous bone (30 %) and bovine bone matrix (BioOss Ò , Geistlich Pharma AG, Wolhusen, Switzerland) (70 %). Kirmeier et al…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic evaluations of vertical graft height after maxillary sinus floor elevation are well documented [8,9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. However, these studies differ in radiographic methods, using panoramic radiographs [18, 22-24, 29, 33], computed tomography (CT) [9,21,23,26] or cone beam computed tomography (CBCT) [8,22,32,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13], Berberi A. [10], Nishida T. [8], Dellavia [18]followed up thevolumetric changes occurring after a sinus floor augmentation procedure over a 6-month period.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of clinical studies using CBCT to follow graft volume changes have demonstrated the potential for applying this technique to assess not only the quantity but also the quality of the osseointegrated graft. [13][14][15][16] And it has recently been reported to be the best clinically available tool for assessing graft volume changes in vivo. 17 CBCT was additionally found to be equally valid to multislice CT in following up osseous volumetric changes in a cleft palate model.…”
Section: Discussionmentioning
confidence: 99%